TANGGGUNG JAWAB PENGURUS TERHADAP AKTA PENDIRIAN/ANGGARAN DASAR YAYASAN SETELAH BERLAKU UU YAYASAN DAN PP NOMOR 63 TAHUN 2008 TENTANG PELAKSANA UU YAYASAN - Syahrul Sitorus; Runtung Runtung; Suhaidi Suhaidi; Keizerina Devi Azwar (USU LAW JOURNAL, 2015)
ABSTRACT One of the legal entity institutions is foundation. It has had its legality since the validation of foundation memorandum of association was obtained from Menhumkam. This validation is required by all foundation, either before or after the Law on Foundation and PP (Government Regulation) No. 63/2008 exists. The result of the research showed that management responsibility established before Law on Foundation and PP No. 63/2008 were in effect was required to adjust its memorandum of association. If it is not adjusted, its legal status is liquidated and closed down. It seems that the government agrees on the foundation legal entity since it still prolongs the foundation operational permit. Management should submit the foundation which does not adjust its memorandum of association to the liquidator to be liquidated. When the management has objection to do this, judicial review on Article 71 of Law on Foundation and Article 39 of PP No. 63/2008 can be filed. The government should make time for adjusting the foundation memorandum of association which has not been adjusted. Keywords: Foundation, Management Responsibility, Memorandum of Association/ Statutes, Property, Government